Strategy for Scanning Peptide-Coding Circular RNAs in Colorectal Cancer Based on Bioinformatics Analysis and Experimental Assays - Chen, Zhanghan; Qi, Zhipeng; He, Dongli; Liu, Jingyi; Xu, Enpan; Li, Bing; Cai, Shilun; Sun, Di; Cheng, Yirong; Shi, Qiang; Zhong, Yunshi (Frontiers in Cell and Developmental Biology, 2022)
Background: Colorectal cancer (CRC) is the third cause of cancer death worldwide. Numerous studies have reported that circular RNAs (circRNAs) have important functions in CRC. It was first thought that circRNAs were non-coding RNA; however, more recently they were discovered to encode peptides and play a pivotal role in cancer development and progression. It was shown that most circRNAs possess coding potential; however, not all of them can truly encode peptides. Therefore, a practical strategy to scan for coding circRNAs is needed. Method: Sequence analyses included open reading frame prediction, coding peptide prediction, and the identification of unique sequences. Then, liquid chromatography-tandem mass spectrometry was introduced to detect sequences of circRNAs with coding potential. Experimental assays were used to verify the coded peptides. Finally, the functions of the circRNAs were primarily explored. Result: An efficient strategy for searching circRNAs with coding potential was created. We verified this schedule using public databases, and two of these circRNAs were selected for further verification. We used commercial antibodies that can also identify the predicted peptides to test the coded peptides. The functions of the circRNAs were explored and the results showed that they were mainly involved in the promotion of proliferation and invasion ability. Discussion: We have constructed an efficient strategy of scanning circRNAs with coding potential and preliminarily verified the predicted peptides and functions of these circRNAs. Our strategy helped to identify circRNA-derived peptides and also provided a more convenient pathway for exploring the coding potential of circRNAs.